2003
DOI: 10.1046/j.1525-1497.2003.10425.x
|View full text |Cite
|
Sign up to set email alerts
|

Promotion criteria for clinician-educators

Abstract: It is reassuring that both department chairs and promotion committee chairs value teaching skills and clinical skills as the most important areas of a clinician-educator's performance when evaluating for promotion. However, differences in opinion regarding the importance of several performance measures and the need for improved quality measures may represent barriers to the timely promotion of clinician-educators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
164
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(165 citation statements)
references
References 20 publications
0
164
0
1
Order By: Relevance
“…Publication in peer-reviewed journals is likely to advance the promotion of clinicianeducators and to facilitate the dissemination of effective teaching strategies among medical educators. 1,8,9 Research has shown that consumers of medical education literature find the greatest value in novel, provocative research findings and methodologically sound research; other important features include relevance, feasibility, and connection to a conceptual framework. 21 Use of the MERSQI may enhance methodological quality in evaluating curricula and performing medical education research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Publication in peer-reviewed journals is likely to advance the promotion of clinicianeducators and to facilitate the dissemination of effective teaching strategies among medical educators. 1,8,9 Research has shown that consumers of medical education literature find the greatest value in novel, provocative research findings and methodologically sound research; other important features include relevance, feasibility, and connection to a conceptual framework. 21 Use of the MERSQI may enhance methodological quality in evaluating curricula and performing medical education research.…”
Section: Discussionmentioning
confidence: 99%
“…1 While abstracts presented at national meetings are important for disseminating research findings, limitations include small audiences, the absence of rigorous peer review, and abbreviated presentation of data. A recent Cochrane review found that only 44.5 % of abstracts presented at national meetings were subsequently published in indexed journals.…”
Section: Introductionmentioning
confidence: 99%
“…Third, inform them about what generalist faculty need to succeed, in terms of institutional resources and time commitment, and make sure that recruitment packages reflect that. Fourth, secure generalist representation (including clinician-educators) on departmental promotion committees to speak to the value and complexity of generalist scholarship, and fight to change institutional policies and attitudes of promotion committee leadership, 9 to make sure that individuals seeing patients 80% of the time are not evaluated with the same metric as those primarily doing research. Finally, learn to what each faculty member aspires.…”
mentioning
confidence: 99%
“…Therefore, the standard measure of clinical teachers' achievements is learner's assessments, not publications. 5,6 Surveys of US department and promotion committee chairpersons have revealed that learners' assessments are among the most important criteria for advancing clinician educators. 5,6 Consequently, learner-of-teacher assessments must be trustworthy.…”
mentioning
confidence: 99%
“…Experts have therefore argued for multi-source assessments that incorporate peer and learner ratings, faculty development, educational service, and awards. 5,11,12 Moreover, we must distinguish between using teaching assessments for administrative decisions versus research. The purpose of research, which traditionally incorporates both quantitative and qualitative methods, is to reveal new knowledge about clinical teachers.…”
mentioning
confidence: 99%